2006
DOI: 10.1111/j.1600-6143.2006.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone Suppresses the Function and Promotes Apoptosis of Plasmacytoid Dendritic Cells

Abstract: Organ transplant recipients are highly susceptible to viral infections early after transplantation. Plasmacytoid dendritic cells (PDC) play a major role in antiviral immunity. Therefore, we determined the numbers of circulating PDC after liver transplantation (LTX) and established the effects of immunosuppressive drugs on PDC survival and function. PDC were determined longitudinally in 13 LTX recipients treated with prednisone and cyclosporin or tacrolimus. Purified PDC were cultured with or without clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 43 publications
4
46
0
Order By: Relevance
“…An increased maturational response of pDCs in severe COPD, as suggested by FREEMAN et al [17], could also explain the lower numbers of BDCA-2-positive pDCs. Finally, the use of inhaled and systemic corticosteroids by patients with severe and very severe COPD could contribute to the reduced number of pDCs in this study, as these drugs are known to induce apoptosis in circulating and tissue-resident pDCs [36][37][38][39]. This lower number of pDCs in lymphoid follicles of patients with very severe COPD treated with inhaled steroids could be linked to the observed association of increased risk of pneumonia and the use of inhaled corticosteroids in patients with COPD [40].…”
Section: Discussionmentioning
confidence: 79%
“…An increased maturational response of pDCs in severe COPD, as suggested by FREEMAN et al [17], could also explain the lower numbers of BDCA-2-positive pDCs. Finally, the use of inhaled and systemic corticosteroids by patients with severe and very severe COPD could contribute to the reduced number of pDCs in this study, as these drugs are known to induce apoptosis in circulating and tissue-resident pDCs [36][37][38][39]. This lower number of pDCs in lymphoid follicles of patients with very severe COPD treated with inhaled steroids could be linked to the observed association of increased risk of pneumonia and the use of inhaled corticosteroids in patients with COPD [40].…”
Section: Discussionmentioning
confidence: 79%
“…24 Viability of freshly sorted normal blood pDC (Ͼ 99% purity) after 24 hours in culture medium was consistently Ͻ 30% and was further decreased in a dose-dependent manner in the presence of the natural GC hydrocortisone ( Figure 1A), confirming that pDCs are sensitive to GC-induced apoptosis. 14 We asked whether IL-3, which promotes pDC survival and activation, 25 was able to protect pDCs from GC-induced apoptosis. IL-3 (10 ng/mL) promoted good pDC viability after 24 hours of culture as assessed by trypan blue exclusion of dead cells ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…8 A major mechanism by which GCs mediate anti-inflammatory responses is to induce apoptosis of several immune cell types, 9 including eosinophils, 10 activated T cells, 11 thymocytes, 3,12 monocytes, 4 dendritic cells (DCs), 13 and plasmacytoid predendritic cells (pDCs). 14 Induction of apoptosis by GCs appear to be more restricted to immune cells, because GCs have antiapoptotic effects on epithelial cells, such as mammary gland, hepatocytes, and ovarian follicular cells. 15,16 Another mechanism is that GCs inhibit the production of proinflammatory cytokines, such as tumor necrosis factor-␣ (TNF-␣), interleukin-1 (IL-1), IL-6, and IL-12, by interfering with the nuclear factor B (NFB) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Patients and healthy volunteers treated with corticosteroids show a decrease in the levels of circulating pDCs (45). It has been shown that glucocorticoid treatment of human pDCs can induce apoptosis via the extrinsic pathway (46). Tumor-induced DC apoptosis.…”
Section: Regulation Of DC Apoptosismentioning
confidence: 99%